Post-WWI Balkan Revival: The Ancient Greek Legacy in the Sokol Movement 1919–1924: Ancient Greek Legacies in the Sokol Movement 1919–1924 - Pavlović, Jovana V.; Filipović, Milica G.; Popović, Jasna D. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
Statistical analysis of relevant resources reveals the expansion of the Yugoslav and Czech Sokol Movements from 1919 to 1924, a period after World War I marked by a cultural and economic crisis. The ideological orientation of the Balkan Sokol movement towards strengthening integral Yugoslavism and realizing ideas of cosmopolitanism coincides with the two main domestic and foreign political tendencies of the newly founded Kingdom of the Serbs, Croats, and Slovenes. This paper aims at defining the ancient Greek legacy inherent in the socio-political role of Sokolski glasnik [Sokol Gazette] in the early post-war period. The Sokol national movement, a sports and political organization based on 1919 foundations, lasted almost continuously until the beginning of World War II.
Keywords: antiquity; South Slavic falconry; 1919–1924 period; integral Yugoslavism; Sokolski glasnik